Effectiveness of Miana Leaves (Plectranthus scutellaroides) as a Natural Dye in the Identification of Soil Transmitted Helminth (STH) Eggs - Samosir, Erica; Rahmah, Lestari (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: The use of natural dyes in microscopic examinations, such as the identification of Soil-Transmitted Helminth (STH) eggs, provides a safer and more environmentally friendly alternative. Miana Leaves (Plectranthus scutellaroides), which contain high levels of anthocyanins, have the potential to serve as an effective natural dye for staining STH eggs in fecal samples. Objectives: This study aims to evaluate the staining efficacy of miana leaf extract (Plectranthus scutellaroides) in identifying STH eggs by comparing different extract concentrations. Materials and Method: An experimental approach with descriptive data analysis was employed. Various concentrations of miana leaf extract (1:1, 1:2, and 1:3 ratios with distilled water) were tested on fecal samples positive for STH eggs. Results: The 1:2 concentration of miana leaf extract yielded optimal contrast and clear visualization of STH egg morphology, while the 1:1 concentration resulted in excessive staining and the 1:3 concentration produced pale staining. Conclusions: Miana leaf extract, particularly at a 1:2 concentration, is effective as a natural stain for STH egg identification. Further research should explore its application in broader parasitological diagnostic contexts.